High-visfatin levels in women with polycystic ovary syndrome: evidence from a meta-analysis. (3rd October 2015) - Sun, Yifan; Wu, Zhitong; Wei, Lili; Liu, Chunming; Zhu, Shengbo; Tang, Shifu
Abstract: Objective : Previous studies regarding visfatin levels in women with polycystic ovary syndrome (PCOS) showed conflicting results. To evaluate the visfatin levels in PCOS, a meta-analysis was performed. Methods : A comprehensive literature search of eligible studies in Embase, Pubmed and the Cochrane Library was undertaken through November 2014. Standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated to estimate the strength of the association. Results : A total of 1341 subjects (695 cases and 646 controls) were included in this meta-analysis. The pooled analysis results indicated that the visfatin levels were significantly higher in PCOS patients than that of controls (SMD = 1.19, 95% CI 0.77–1.60, p  = 0.000). The results from stratified analysis and univariate analysis suggested that high-visfatin levels were not related to body mass index (BMI), insulin resistance (IR) and total testosterone ratio. Significant heterogeneity was observed in all analysis. Conclusion : Our results indicate that high-circulating visfatin level is an intrinsic characteristic of PCOS, which suggests visfatin could be a potential biomarker for PCOS.